Bradykinin’s carbamylation as a mechanistic link to impaired wound healing in patients with kidney dysfunction - Marta Kaminska; Urszula Kałucka; Janka Babickova; Małgorzata Benedyk-Machaczka; Eleni Skandalou; Melissa M. Grant; Hans-Peter Marti; Piotr Mydel (BMC Biology)
Abstract Background Uremic impairment of wound healing is a well-established phenomenon, however the etiology of this condition continues to be a medical enigma. Carbamylation, posttranslational modification (PTM) occurring with high frequency in uremic milieu, is known to have impact on structural and functional properties of proteins and peptides. Herein we show that carbamylation of the members of kinin-kallikrein system, that play an essential role in wound healing process, results in its aberrant functionality and impedes the complex process of tissue regeneration in uremic patients. Results Through enzymatic assays we demonstrate that carbamylation of kininogen results in aberrant bradykinin generation. We confirmed that bradykinin is efficiently carbamylated in uremic conditions and, alternatively, by activated neutrophiles. Moreover, this modification affects proteolytic cleavage of the peptide, potentially leading to the accumulation of the carbamylated form. Modified peptide demonstrated lower affinity toward its receptors. Carbamylation diminished bradykinin’s ability to stimulate expression of the B1 receptor and cytokines essential in wound healing process. Carbamylated bradykinin was significantly less potent in promoting angiogenesis and keratinocyte motility as compared to the native form. In the in vivo murine model of wound healing, we observed impaired collagen fiber production and delayed re-epithelialisation in the presence of carbamylated form. Conclusions Carbamylation-driven impairment of wound healing is a mechanistic link to wound persistence in uremia. Importantly, production of carbamylated bradykinin in localized inflammatory milieus could be a significant contributor to delayed wound healing and formation of chronic wounds in diabetes or psoriasis.